The Godless Girl - Marks, Martin (Treasures III: Social Issues in American Film (1900-1934), 2007)
Cecil B. De Mille bid goodbye to the silent era with "The Godless Girl", an epic about the conflict between atheists and Christians in an American high school. Although the film featured many of De Mille's silent film trademarks - epic sequences, piety and the exploitation of contemporary issues - it also represents a surprisingly mature treatment of its central religious conflict. The latter makes the film particularly timely today, in an era when heated political debates continue to inform the political scene. [www.tcm.com]